The expression and association of MATK in chronic hypoperfusion patients with white matter hyperintensity - Zhao, Ming; Zhang, Jiayue; Yang, Qianqian; Chen, Lei; Shen, Hongjian; Pu, Yingyan; Wei, Wei; Han, Yi; Zhang, Ping (Frontiers in Aging Neuroscience, 2025)
BackgroundChronic cerebral hypoperfusion (CCH) is a key contributor to vascular cognitive impairment (VCI). Patients with CCH frequently exhibit white matter hyperintensities (WMH) on MRI. This study investigated the expression and clinical relevance of megakaryocyte-associated tyrosine kinase (MATK) in CCH patients with WMH.MethodsWe recruited 42 anterior circulation stenosis patients with CCH and WMH (CCH-WMH group) and 45 age-matched healthy controls. MATK mRNA expression in peripheral blood mononuclear cells (PBMCs) was quantified using qPCR. WMH severity was graded using the Fazekas scale. Correlations between MATK expression and imaging/clinical parameters were analyzed using Pearson’s correlation and logistic regression. Diagnostic performance was assessed via ROC analysis.ResultsMegakaryocyte-associated tyrosine kinase expression was significantly downregulated in the CCH-WMH group versus controls (1.20 ± 0.99 vs. 1.84 ± 0.87; P < 0.01). MATK levels showed a strong negative correlation with Fazekas scores (R2 = 0.3405, P < 0.001). Multivariate regression identified MATK as independently associated with WMH (aOR = 0.492; 95% CI: 0.262–0.923; P = 0.027). ROC analysis demonstrated moderate diagnostic accuracy for WMH (AUC = 0.743; 95% CI: 0.637–0.849).ConclusionReduced peripheral MATK expression correlates with WMH severity in CCH patients and may serve as a potential diagnostic biomarker.